Biofertilization of topinambur with Azospirillum brasilense and native mycorrhical fungi, cultivated in the Central Valley of Catamarca, Argentina - Di Barbaro, Maria Gabriela (2021)
To evaluate the effect of Azospirillum and mycorrhizal soil fungi on the nutrition of the Jerusalem artichoke crop (Helianthus tuberosus L.), determinations of agronomic parameters and the health status of the plants were carried out under field conditions. The tests were carried out, at the time of the implantation of the culture: the ?seeds? were inoculated with A. brasilense and with native mycorrhizal fungi, generating four treatments including the control and the co-inoculation of the consortium of the microorganisms under study (T0: control or uninoculated control; T1: inoculation with native A. brasilense; T2: inoculation with native mycorrhizal fungi and T3: joint inoculation with A. brasilense and native mycorrhizal fungi). The results indicate that co-inoculation with A. brasilense and native mycorrhizal fungi, significantly increased plant growth in height, leaf area, biomass, dry matter, and yields. It was determined that the application of the selected microorganisms has a promoting effect of plant growth, increasing the growth and productivity of the topinambur crop.